"Choose Today, Live Tomorrow": A Content Analysis of Anti-Substance Use Messages Produced by Adolescents. Issue 6 (3rd June 2019) - Peña-Alves, Stephanie; Greene, Kathryn; Ray, Anne E.; Glenn, Shannon D.; Hecht, Michael L.; Banerjee, Smita C.
Abstract : Adolescent-produced anti-substance use messaging is an increasingly popular and effective prevention strategy. However, little is known about the content of these messages and the production elements adolescents use to bring that content to life. In this article, we present a content analysis of 95 anti-substance use messages developed by 4-H club members across nine U.S. states as part of their participation in the media literacy program REAL media. Posters and videos were content-analyzed for target substance, prevention goal, message form, message content, persuasion strategies, and production elements. Results of the content analysis revealed that combustible tobacco (smoking) was the most popular target substance in the sample among the choices of alcohol, marijuana, e-cigarettes, and chewing tobacco. More youth developed messages with the goal of preventing substance use, rather than stopping current use. Slogans were used in the majority of messages, and nearly all messages took an informational form, rather than narrative or statistical form. Persuasion strategies covered in the curriculum, including fun with the group, unexpected, style, and endorsement were scantily used. Finally, results showed that production value was high in this sample, reflected by the extensive use of color and variety of fonts and font sizes. Implications for future media literacy interventions and research are discussed.